Errors in estimating reproductive parameters with macroscopic methods: a case study on the protogynous blacktip grouper Epinephelus fasciatus (Forsskål 1775) - Ken Longenecker; Ross Langston; Juliaeta Mamesah; Yuliana Natan; Maureen Pattinasarany; Abdul W. Radjab; Ahmad Romdon; Fismatman Ruli; Prandito Simanjuntak; Febby L. Sinaga; Gino V. Limmon; Erik C. Franklin (Journal of Fish Biology, 2024)
A size‐based, histological analysis of the reproductive life history of the blacktip grouper, Epinephelus fasciatus (Forsskål 1775), was conducted in Indonesia to evaluate the error rate associated with macroscopic reproductive analysis. Histological results indicated that E. fasciatus was protogynous with female L 50 at 13.4 cm total length (L T ) and a size at sexual transition of 22.0 cm L T . The weight–length relationship for the species was W = 0.011 L 3.13 . Overall sex ratios were significantly female biased, operational sex ratios were significantly male biased, and sex ratios of mature individuals varied predictably with length from female to male dominance as size increased. No significant relationship between length and batch fecundity was found. The population has a spawning period from February to August. Overall, 54.4% of macroscopic evaluations were incorrect compared to histological results. Of the errors, 14.8% were a failure to detect ovotestes, 12.7% were classifying non‐gonadal tissue as ovary or testis, 12.2% were misclassifying sex, and 12.7% were misclassifying maturity status. However, the largest source of error (47.7%) was from misclassifying both sex and maturity status. Of these, 92.9% were macroscopically classified as immature females, but were histologically confirmed to be mature males. Compared to histological results, the only accurate macroscopic results were the absence of a sex‐based difference in weight–length relationship and spawning seasonality estimated by a gonadosomatic index (February–June). The use of macroscopic methods to estimate reproductive life‐history parameters for sex‐changing reefes fish may introduce significant inaccuracies and misinterpretations. Of the parameters estimated by histological methods, size at maturity, size‐specific sex ratios, and spawning seasonality have the greatest potential to inform local fishery management policy.